The Influence of Health Consciousness, Food Quality, Country of Origin and Consumer Preference Toward Purchase Decision to The American Fast Food Restaurants - admin, Muhammad Recky Reynaldy B1024161006 (Jurnal Manajemen Update, 2020)
ABSTRACTÂ The purpose of this research is to analyze the influence of Health Consciousness, Food Quality, Country of Origin and Consumer Preference Toward Purchase Decision to The American Fast Food Restaurants in Pontianak City. Nowadays, most of food consumption trend in urban parts of developing countries is that mostly consumers tend to eat more meals outside of their homes and most of the growth in away-from-home eating has been in the fast food sector. The ease of getting fast food on the market makes it provides a numerous of foods based on preference and purchasing power of consumers. In addition, the food processing is getting easier, faster and preparation is perfect for consumers who are always busy. From this point, we may conclude that fast food restaurants should know how customers make their Purchase Decision. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research are H1: Health Consciousness influences Consumer Preference to the Purchase Decision at the Fast Food Restaurants (KFC, A&W and Texas Chicken) in Pontianak City, H2: Food Quality influences Consumer Preference to the Purchase Decision at the Fast Food Restaurant (KFC, A&W and Texas Chicken) in Pontianak City, H3: Country of Origin influences Consumer Preference to the Purchase Decision at the Fast Food Restaurant (KFC, A&W and Texas Chicken) in Pontianak City, H4: Consumer Preference influences Purchase Decision to the Fast Food Restaurants (KFC, A&W and Texas Chicken) in Pontianak City. The result shows that H1, H3, and H4 are rejected and only H2 is accepted.Â Â Â Â Â  Keywords: Health Consciousness, Food Quality, Country of Origin, Consumer Preference, Purchase Decision.Â Â BibliographyGhozali. (2011). 105.Ahmed et al. (2004). â€œDoes country of origin matter for low-involvement productsâ€,. International Marketing Review, Vol. 21 No. 1, 102-120.Amstrong, P. K. (2007). Prinsip- Prinsip Marketing. Jakarta: Salemba Empat.Anderson, T., & Cunningham, H. (1972). Gauging foreign product promotion. Journal of Advertising Research, 12(1), 29-34.Basil et al. (2013). The marketing mix element as determinants of consumerâ€™s choice of made-in-Nigeria shoes in Cross River state. European Journal of Business and Management, 141-147.Batra et al. (2000). Effects of brand local and non-local origin on consumer attitudes in developing countries. Journal of Consumer Psychology, 9(2), 85-93.Beneke et al. (2013). "The influence of perceived product quality, relative price and risk on customer value and willingness to buy: a study of private label merchandise",. Journal of Product & Brand Management, Vol. 22 No. 3, 218-228.Bergh et al. (1999). Advertising Principles: Choice, Challenge, Change. Lincolnwood: Contemporary Publishing Group, IL: NTC.Blackwell et al. (2001). Consumer Behavior. Ohio: South-Western Thomas Learning, Mason.Bryhni et al. (2002). "Consumer Perception Of Pork In Sub Continent.".Cardelo et al. (2007). â€œConsumer perceptions of foods processed by innovative and emerging technologies a conjointanalytic study.â€. Innovative Food Science and Emerging Technologies 8(1), 73-83.Chaipradermsak, T. (2007). The influential factors on consumersâ€™ purchasing decision in Bangkok pet retailing business.Chand et al. (2011). â€œAvailability and accessibility of healthier options and nutrition information at New Zealand fast food reataurants . Appetite, 227-233.Cimadon et al. (2010). Dietary Habitt and Risk Factors.Clark, L., & Watson, D. (1993). Constructing validity: Basic issues in objective scale development. Psychological Assessment, 7(3), 309-319.Dantas et al. (2004). â€œThe effect of packaging on the perception of minimally processed products.â€. Journal of International Food & Agribusiness Marketing, 16(2), 71-83.David, L. L., & Albert, J. D. (2002). Consumer Behavior. New Delhi: McGraw Hill.Deliza et al. (1999). â€œAn investigation using the repertory grid and focus group methods of the package features affecting consumer perception of fruit juice.â€. Brazilian Journal of Food Technology 2, 63-71.Delwiche, J. (2004). The impact of perceptual interactions on perceived flavour. Food Quality and Preference. 137-146.Deshpande et al. (2009). Factors influencing healthy eating habits among college students: An application of the health belief model. Health Marketing Quarterly, 145-164.Din et al. (2012). Customer perception on nutritional information in restaurant menu. Procedia-Social and Behavioral Sciences, 413-421.Din et al. (2012). Customer perception on nutritional information in restaurant menu. Procedia-Social and behavioral sciences, 413-421.Engel, & et al. (1995). Consumer Behavior. Florida: The Dryden Press.Fife et al. (2007). Measuring customer preferences for drinking water services. Journal Techneauwa, 1-48.Fitzgerald et all. (2013). Self-efficacy for healthy eating and peer support for unhealthy eating are associated with adolescentsâ€™ food intake. Appetite, 48-58.Ghozali. (2011). 160.Ghozali. (2011). 98.Ghozali. (2011). 97.Glanz et all. (1998). Why Americans eat: taste, nutrition, cost, convenience, and weight control concerns as influences on food consumption. Journal of the Academy of Nutrition and Dietetics, 1118-1126.Gould et al. (1998). Consumer Attitudes Toward Health and Health Care: A Differential Perspective. Journal of Consumer Affairs, 96-118.Goyal, & Singh. (2007). Consumer Perception about fast food in India. Journal of Hospitality& Tourism, 413-421.Gracia et al. (2007). Market segmentation and willingness to pay for organic products in Spain. International Food and Agribusiness Management Review, 3(1), 207-226.Han, C. M. (1990). â€œCountry image: halo or summary construct?â€. Journal of Marketing Research,26 (5), 222-9.Han, C. M., & Terpstra, V. (1998). Country-of-origin effects for uni-national and bi-national. Journal of International Business Studies, 235-255.Henseler, & Ringle. (2009).Hox, J. J., & Bechger, T. M. (2011).Hox, J., & Bechger, T. (2011).Jalal, H. R. (2018). An examination of the factors affecting consumerâ€™s purchase decision in the Malaysian Retail Market. 3-8.Jalal, R. H. (2017). An examination of the factors affecting consumerâ€™s purchase decision in the Malaysian retail market.Jang et al. (2011). Generation Y consumersâ€™ selection attributes and behavioral intentions concerning green restaurants. International Journal of Hospitality Management, 803-811.Kaynak, E. (1982). Marketing In The Third World. New York: Preager.Kaynak, E., & Safak , A. (1996). Consumers preferences for Fast Food Outlets in a Developing Country. Journal of Euro Marketing, 99.Kaynank, E. (2006). Consumer Preference for Fast Food.Khuong, M. N., & Duyen, H. T. (2016). Personal Factors Affecting Consumer Purchase Decision Towards Men Skin Care Products. International Journal of Trade, Economics and Finance vol 7.Kim et al. (2013). Does perceived restaurant food healthiness matter? Its influence on value, satisfaction and revisit intentions in restaurant operations in South Korea. International Journal of Hospitality Management, 397-405.Kotler, P., & Levy, S. J. (1969). Broadening the Concept of Marketing. Journal of Marketing, 10-15.Malhota, N. K. (2010). Marketing Research: An Applied Orientation Sixth Edition Pearson Education. Affairs, 96-118.Malhotra, N. K. (1986). Modeling Store Choice Based On.Martin, N., & Morich, K. (2011). Unconscious mental processes in consumer choice: Toward a new model of consumer behavior. Journal of Brand Management, 483-505.Moreau et al. (2001). â€œWhat is it?â€ categorization flexibility and consumersâ€™ responses to really new products". Journal of Consumer Research, 489â€“498.Oura, Y. K., H, Y. A., & Sato, K. (2022). â€œEstimation for brand power on fresh vegetables andfruits producing districts with choice-based conjoint analysisâ€. Japanese Journal of Farm Vol 40 no 1, 106-111.Parkvithee, N., & Miranda, M. (2012). The interaction effect of country-of-origin, brand equity and purchase involvement on consumer purchase intentions of clothing labels. Asia Pacific. Journal of Marketing and Logistics, 24(1), 7-22.Peri, C. (2006). The universe of food quality, Food Quality and Preference. 3-8.Qin et al. (2009). Perceived service quality in fast- food restaurants: Empirical evidence from China. International Journal o of Quality and Reliability Management, 424-437.Roth, K. P. (2009). â€œAdvancing the country image constructâ€. Journal of Business Research Vol. 62, No.7, 726-740.Roth, M., & Romeo, J. (1992). â€œMatching product and country image perceptions: a framework for managing country-of-origin effectsâ€. Journal of International Business Studies, Vol. 23 No. 3, 477-497.Saeed. (1994). â€œConsumer evaluation of products in a global market". Journal of International Business Studies Vol. 25 No. 3, 579-604.Schiffman, L. G., & Kanuk, L. L. (2007). Consumer Behavior. New Jersey: Prentice-Hall.Sebastianelli, R., & Tamimi, N. (2002). â€œHow product quality dimensions relate to defining qualityâ€. International Journal of Quality and Reliability Management, Vol. 19 No 4, 442-453.Shankarmahesh, M. (2006). Consumer ethnocentrism: An integrative review of its antecedents and consequences. International Marketing Review, 23(2), 146-172.Suhaily, L., & Darmoyo, S. (2017). EFFECT OF PRODUCT QUALITY, PERCEIVED PRICE AND BRAND IMAGE ON PURCHASE DECISION MEDIATED BY CUSTOMER TRUST(Study On Japanese Brand Electronic Product). Jurnal Manajemen/Volume XXI, No. 02, 179-194.Tandon et al. (2011). â€œThe Impact of Menu Labeling on Fast Food Purchases for Children and Parentsâ€. American Journal of Preventive Medicine, 434-438.Tandon et al. (2011). â€œThe Impact of Menu Labeling on Fast Food Purchases for Children and Parentsâ€. American Journal of Preventive Medicine, 434-438.Teisl et al, .. (2003). Measuring the welfare effects of nutrition information. American Journal of Agricultural Economics, 133-149.Teisl et al. (2003). Measuring the welfare effects of nutrition information. American Journal of Agricultural Economics, 83(1), 133-149.Teisl et al. (2003). Measuring the welfare effects of nutrition information. American Journal of Agricultural Economics, 83(1), 133-149.Teisl et al. (2003). Measuring the welfare effects of nutrition information. American Journal of Agricultural Economics, 133-149.Ubeja, S. K., & Jain, D. (2013). A Study of Consumers' Towards Branded & Loose Tea. Pacific Business Review International, 19-28.Vaida PilinkienÄ—, R.-J. K. (2013). E-BUSINESS AS A SOURCE OF COMPETITIVE ADVANTAGE.Vaida Pilinkiene1, R.-J. K. (2013). E-BUSINESS AS A SOURCE OF COMPETITIVE ADVANTAGE. ECONOMICS AND MANAGEMENT.Zeng et al. (2008). (Application of hierarchical model in willingness to pay for food safety:Consumer survey of willingness to pay for mooncake additive). (Journal of Agrotechnical Economics), (1), 84-90.Â Â